Enhanced peripheral visual processing in congenitally deaf humans is supported by multiple brain regions, including primary auditory cortex - Scott, Gregory D.; Karns, Christina M.; Dow, Mark W.; Stevens, Courtney; Neville, Helen J. (Frontiers in Human Neuroscience, 2014)
Brain reorganization associated with altered sensory experience clarifies the critical role of neuroplasticity in development. An example is enhanced peripheral visual processing associated with congenital deafness, but the neural systems supporting this have not been fully characterized. A gap in our understanding of deafness-enhanced peripheral vision is the contribution of primary auditory cortex. Previous studies of auditory cortex that use anatomical normalization across participants were limited by inter-subject variability of Heschl’s gyrus. In addition to reorganized auditory cortex (cross-modal plasticity), a second gap in our understanding is the contribution of altered modality-specific cortices (visual intramodal plasticity in this case), as well as supramodal and multisensory cortices, especially when target detection is required across contrasts. Here we address these gaps by comparing fMRI signal change for peripheral versus perifoveal visual stimulation (11-15° vs. 2°-7°) in congenitally deaf and hearing participants in a blocked experimental design with two analytical approaches: a Heschl’s gyrus region of interest analysis and a whole brain analysis. Our results using individually-defined primary auditory cortex (Heschl’s gyrus) indicate that fMRI signal change for more peripheral stimuli was greater than perifoveal in deaf but not in hearing participants. Whole-brain analyses revealed differences between deaf and hearing participants for peripheral versus perifoveal visual processing in extrastriate visual cortex including primary auditory cortex, MT+/V5, superior-temporal auditory and multisensory and/or supramodal regions, such as posterior parietal cortex, frontal eye fields, anterior cingulate, and supplementary eye fields. Overall, these data demonstrate the contribution of neuroplasticity in multiple systems including primary auditory cortex, supramodal and multisensory regions, to altered visual processing in congenitally deaf adults.